Academic discourse - Flowerdew, John (Harlow, England : Longman, 2002)
This book focuses on English for academic purposes. Professor John Flowerdew demonstrates the scope, theoretical issues and pedagogical concerns of discourse analysis within academic contexts.
Introduction: Approaches to the Analysis of Academic Discourse in English / John Flowerdew -- pt. I. Genre Analysis -- 1. Generic View of Academic Discourse / Vijay K. Bhatia -- 2. Disciplinary variation in abstracts: The case of Wildlife Behaviour and Conservation Biology / Betty Samraj -- 3. Generic moves in Ph. D. thesis Introductions / David Bunton -- 4. Introductory concepts and'cutting edge' theories: Can the genre of the textbook accommodate both? / Alison Love -- pt. II. Corpus-based Studies -- 5. Corpus-Based Analyses in EAP / Lynne Flowerdew -- 6. Activity and Evaluation: Reporting practice in academic writing / Ken Hyland -- 7. Corpora and corpus analysis: new windows on academic writing / Christopher Tribble -- 8. Integrated and Fragmented Worlds: EAP Materials and Corpus Linguistics / John M. Swales -- pt. III. Contrastive Rhetoric -- 9. Contrastive Rhetoric: An Expanding Paradigm / Shirley E. Ostler -- 10. Epistemic modality in argumentative essays of second-language writers / Tony McEnery and Nazareth Amselom Kifle -- 11. Packed houses and intimate gatherings: Audience and rhetorical structure / Sally Burgess -- 12. 'Selling' or'telling'? The issue of cultural variation in research genres / Tatyana Yakhontova -- pt. IV. Ethnographic/Naturalistic Approaches -- 13. Ethnographically inspired approaches to the study of academic discourse / John Flowerdew -- 14. Investigating writing development in an academic English Language curriculum / Desmond Allison and Wu Siew Mei -- 15. L2 case discussion in business: An ethnographic investigation / Jane Jackson -- 16. Framing and Text Interpretation Across Languages and Cultures: A Case Study / Joyce Bell.
Includes bibliographical references (pages 302-332) and indexes.
Keywords: Discourse analysis; Scholars -- Language; Rhetoric; Sachtext; Wissenschaftssprache; Kontrastive Textlinguistik; Rhetorik; Textproduktion; Fachsprache; Textsorte; Englisch